Polydopamine-modified dual-ligand nanoparticles as highly effective and targeted magnetic resonance/photoacoustic dual-modality thrombus imaging agents - Zhang Y (Dove Medical Press, 2019)
Yu Zhang1,2, Yixin Zhong1,2, Man Ye1, Jie Xu1, Jia Liu1, Jun Zhou1, Shike Wang1, Dajing Guo1, Zhigang Wang2, Haitao Ran2 1Department of Radiology, The Second Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 2Chongqing Key Laboratory of Ultrasound Molecular Imaging, Department of Ultrasound, The Second Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of ChinaCorrespondence: Haitao RanDepartment of Ultrasound, The Second Affiliated Hospital of Chongqing Medical University, No. 74 Linjiang Road, Yuzhong District, Chongqing 400010, People’s Republic of ChinaEmail rht66@163.comDajing GuoDepartment of Radiology, The Second Affiliated Hospital of Chongqing Medical University, No. 74 Linjiang Road, Yuzhong District, Chongqing 400010, People’s Republic of ChinaTel +86 236 369 3537Email guodaj@hospital.cqmu.edu.cnBackground: Platelet activation and subsequent aggregation are the initial stages of thrombosis. A molecular probe that specifically targets activated platelets and remains retained under high shear stress in vivo can enhance the imaging effect to achieve early and accurate diagnosis.Methods and materials: In this study, we constructed nanoparticles (NPs) using polydopamine to carry two peptides that simultaneously bind integrin αIIbβ3 and P-selectin on activated platelets to enhance the targeting of NPs to thrombus.Results: The targeting specificity and binding stability of the NPs on red and white thrombi were demonstrated in vitro using a simulated circulatory device and the targeting effect of the NPs on mixed thrombus was studied by  magnetic resonance (MR)/photoacoustic (PA) dual-modality imaging in vivo. NPs that were surface modified with both peptides have higher selectivity and retention to red and white thrombi in vitro than NPs with a single or no peptide, and the targeting effect was closely related to the number and distribution of activated platelets as well as the structure and type of thrombus. The NPs also have MR/PA dual-modality imaging functionality, significantly enhancing the imaging of mixed thrombus in vivo.Conclusion: These dual-targeted NPs have improved targeting specificity and binding stability to different thrombi under high shear stress and are beneficial for the early diagnosis of thrombosis.Keywords: dual-modality, dual-ligand, targeting effect, thrombus, magnetic resonance imaging, photoacoustic imaging